FACTORS RELATED TO THE INCIDENCE OF LUNG TUBERCULOSIS - Indra Gunawan; Dadang Sulaeman; Fitriani (PHSAJ - Public Health Sebelas April Journal, 2022)
There are 44 patients with pulmonary TB who recovered in 2021 at the Ganeas Health Center based on reporting using the cohort system so that the evaluation is carried out every quarter. For 2021 the recovery rate reached 60,3%, a decrease from the previous year, which was 64,8%. The type of research used is analytic research, with a case control study design, with a population of 117 people and the number of case samples required is 40 samples and the control sample required 40 samples. The sampling method is done by simple random sampling method. There was no relationship between the age of the patient and the cure for pulmonary tuberculosis (p-value 0,199). There is no relationship between the patient's education level and the cure for pulmonary tuberculosis (p-value 0,531). There is a relationship between the patient's knowledge and the cure for pulmonary tuberculosis (p-value 0,000). There is a relationship between the role of the supervisor taking medication with the cure for pulmonary TB (p-value 0,001), in patients with pulmonary TB in the working area of the Ganeas Health Center in 2022. It is expected that health workers will be active in efforts to improve the regularity of treatment for TB patients to increase the cure rate. And it is hoped that students of the Faculty of Health Sciences will play an active role in providing information about pulmonary tuberculosis.